Pérdida de los incisivos centrales superiores y su influencia en el déficit de la articulación de fonemas consonánticos - Jenny Paulina, Banda Chicaiza (2022)
ABSTRACT: The loss of upper central incisors is considered both an esthetic and functional problem of the stomatognathic apparatus. The main objective of this study was to analyze how the absence of the upper central incisors affects the articulation of consonant phonemes, as well as the main causes of the loss of these teeth and the organs involved in speech production. The information was collected from scientific databases such as: Google Schoolar, Pubmed, SciELO, Medlineplus and Elsevier; where 200 articles were obtained; these were subjected to inclusion and exclusion criteria and 60 articles were chosen, each one of them was validated according to the number of citations (ACC), the impact of the journal (SJR) and by quartiles, leaving 50 articles suitable for the development of this literature review. As a result, it was evidenced that, in the group of consonant phonemes, the labiodental phoneme /f/ will have a distortion in its production, as well as in the dental phonemes /d/, /t/; and the alveolar phonemes /l/, /n/ will have no alteration and the alveolar phonemes /r/, /s/ will suffer alteration at the time of their production.